Postagrogenic phytocenoses of the Volga‐Oka interfluve, Russia - T. A. Trifonova; S. A. Shoba; N. V. Mishchenko; E. P. Bykova; P. S. Shutov; O. V. Saveliev; R. V. Repkin (Юг России: экология, развитие, 2022)
Aim. On the basis of factual material, an assessment was made of the state of land previously (more than 15 years ago) developed as arable land and "abandoned" to date.Material and Methods. Control plots located in different landscape provinces of the Volga‐Oka interfluve were compared in terms of the state of the vegetation cover, as well as the type of overgrowth.Results. Three types of overgrowing of postagrogenic lands characteristic of the initial and intermediate stages of overgrowing of pre‐climax communities have been identified: overgrowing of fields associated with a change in land use; overgrowing of fields with a nearby forest; and overgrowing of fields without a closely located forest.Conclusion. It was shown that as a result of the overgrowing of agricultural lands, the species diversity of plant communities is sharply reduced, the restoration of which is very problematic in the foreseeable future. While postagrogenic phytocenoses are able to gradually restore their production potential to the level of natural phytocenoses, however, their productivity will occur with a different species composition of herbaceous plants with low biodiversity.